HOW TO TEACH LEGAL FRENCH TO LITHUANIAN SPEAKERS - Parent, Arnaud (Vertimo studijos, 2017)
Legal language has its own technical terms that a translator has to know. This article considers some specificities of French and Lithuanian legal terms as well as specific turns of the sentence and the ways to train students to recognize and use them.